Does personality still matter in e-commerce? How perceived hubris influences the assessment of founders' trustworthiness using the example of reward-based crowdfunding - Janina Sundermeier; Tyge-F. Kummer (Electronic Markets, 2022)
Reward-based crowdfunding broadens the scope of e-commerce transactions, as prototypical products are pre-sold under conditions of considerable uncertainty. To date, we know little about the mechanisms that underlie decisions to back reward-based crowdfunding campaigns. However, it is likely that startup founders' possibility of showcasing their personalities in video pitches signals their trustworthiness, particularly, as other features, such as quality seals and customer testimonials, are often unavailable. We use signaling theory to reinforce the move from a feature-oriented perspective to a signaling perspective, as signals can transmit information about startup founders' otherwise imperceptible qualities and abilities. Based on a survey ( N 0.167em=0.167em108), we investigate how perceived hubris – proven to be particularly salient in startup contexts – influences the funding decision of potential backers. We find that abilities and legitimacy of a startup founder are rated positively when s/he is perceived as hubristic. These results have implications for crowdfunding campaigns and highlight the relevance of personality traits in electronic markets.
Keywords: D81; M13; 620; Reward-based crowdfunding; Personality traits; Hubris; Survey; Intuitive information processing